A Case Report of Hepatic Rupture Associated with Hellp Syndrome - M, Sena-Martins; PGS, Daher; V, Tadini; GB, Loprete; T, Nakata; L, Mantuan; NR, Stefani; CR, Vissechi-Filho; GN, Souza; M, Sakita (Clinical Journal of Obstetrics and Gynecology, 2025)
HELLP syndrome is a severe variant of preeclampsia, characterized by hemolysis, elevated liver enzymes, and low platelet count, often resulting in significant maternal and fetal morbidity. One of its most catastrophic but rare complications is hepatic rupture, typically secondary to the development of a subcapsular liver hematoma. This case report describes a patient with hepatic rupture associated with HELLP syndrome, managed at the Leonor Mendes de Barros Maternity Hospital in São Paulo.